Endometrial thickness assessed by transvaginal ultrasound in transmasculine people taking testosterone compared with cisgender women. Issue 5 (November 2022) - Asseler, Joyce D.; Caanen, Mirte R.; Verhoeven, Marieke O.; Huirne, Judith A.F.; Goddijn, Mariëtte; van Dulmen-den Broeder, Eline; Overbeek, Annelies; Lambalk, Cornelis B.; van Mello, Norah M.
Highlights: Endometrial thickness in trans masculine persons is lower compared to cis women No endometrial abnormalities were detected by ultrasound in either group Burdensome endometrial screening may not be necessary in trans masculine persons Abstract: Research question: What is the endometrial thickness of endometrium exposed to testosterone in transmasculine people compared with unexposed endometrium in cisgender women as determined by transvaginal ultrasound (TVU)? Design: Single centre, cross-sectional cohort study conducted the Centre of Expertise on Gender Dysphoria in Amsterdam. Between 2013 and 2015, transmasculine people scheduled for gender affirming surgery (GAS) were included in this study after they provided informed consent. They were undergoing gender affirming hormone therapy (testosterone) for at least 1 year. Endometrial thickness (mm) was measured by TVU in transmasculine people, immediately before their GAS while under general anaesthesia. Cisgender control women from the general population underwent the exact same TVU measurements in an outpatient clinical setting on cycle days 2–5. Result: Fifty-one transmasculine people and 77 controls were included. The mean duration of testosterone use was 30.2 months (SD 8.8). Endometrial thickness was significantly lower in transmasculine people compared with cisgender women: median 3.9 mm (interquartile range [IQR] 2.8–5.1) and 4.9 mm (IQR 4.0–6.3), respectively ( P < 0.001), after correcting for confounding factor (current gonadotrophin releasing hormone agonist use). Conclusions: Endometrial thickness in transmasculine people exposed to testosterone is significantly lower compared with cisgender women without testosterone exposure. These results suggest an absence of endometrial proliferation by exogenous testosterone.